2014
DOI: 10.1128/aem.00254-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of Waterborne Pathogens and Microbial Source Tracking Markers in Paired Agricultural Watersheds under Controlled and Conventional Tile Drainage Management

Abstract: f Surface waters from paired agricultural watersheds under controlled tile drainage (CTD) and uncontrolled tile drainage (UCTD) were monitored over 7 years in order to determine if there was an effect of CTD (imposed during the growing season) on occurrences and loadings of bacterial and viral pathogens, coliphages, and microbial source tracking markers. There were significantly lower occurrences of human, ruminant, and livestock (ruminant plus pig) Bacteroidales markers in the CTD watershed in relation to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…Several Bacteroidales markers have been designed to detect fecal pollution from human (Seurinck et al, 2005), ruminant (Reischer et al, 2006), pig (Mieszkin et al, 2009), and wild animals (Fremaux et al, 2010; Marti et al, 2011a, 2013b). Correlations with the occurrence of human pathogens have been observed (Fremaux et al, 2009; Staley et al, 2012; Marti et al, 2013a; Wilkes et al, 2013, 2014). Ruminant-specific MST markers BacR and CF128, designed by Reischer et al (2006) and Bernhard and Field (2000b), respectively, and the human-specific marker HF183, were found positively correlated to an occurrence of Salmonella cells (Fremaux et al, 2009; Marti et al, 2013a; Wilkes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several Bacteroidales markers have been designed to detect fecal pollution from human (Seurinck et al, 2005), ruminant (Reischer et al, 2006), pig (Mieszkin et al, 2009), and wild animals (Fremaux et al, 2010; Marti et al, 2011a, 2013b). Correlations with the occurrence of human pathogens have been observed (Fremaux et al, 2009; Staley et al, 2012; Marti et al, 2013a; Wilkes et al, 2013, 2014). Ruminant-specific MST markers BacR and CF128, designed by Reischer et al (2006) and Bernhard and Field (2000b), respectively, and the human-specific marker HF183, were found positively correlated to an occurrence of Salmonella cells (Fremaux et al, 2009; Marti et al, 2013a; Wilkes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its potential as a virus indicator is promising. To our knowledge, the studies by Wilkes et al (4,39) are some of the first to report NoV GIII in an agriculture-dominated watershed setting.…”
Section: Detection and Densities Of F-specific Coliphage And Viruses mentioning
confidence: 99%
“…These viruses can contaminate surface waters via wastewater discharge, runoff and drainage from farming operations, and leakage from faulty septic systems (2)(3)(4)(5)(6)(7)(8). With ever-increasing anthropogenic stresses and pressures on surface water resources, identifying the driving factors that govern fecal pollution in open watershed systems and implementing management practices/strategies designed to ultimately reduce infection risks are becoming more crucial (9,10).…”
mentioning
confidence: 99%
“…While most CD studies have focused on nutrient export and crop productivity (Evans et al, 1992;Drury et al, 1996;Skaggs et al, 2012;Sunohara et al, 2014), some recent research has documented the implication of CD for managing environmental fate of microorganisms. For example, Wilkes et al (2014) found that widespread implementation of CD in a watershed can reduce the occurrences of Arcobacter spp., Salmonella spp., and ruminant (livestock-based) Bacteroidales microbial source tracking markers in surface water. Also, Frey et al (2013) found that CD can significantly lower bacteria loads transmitted to surface water following the land application of liquid swine manure.…”
Section: Introductionmentioning
confidence: 98%